WELL AND OUTCROP CORRELATION IN THE EASTERN PART OF AKIMEUGAH BASIN, PAPUA: MESOZOIC PLAY POTENTIAL - Rakhmat Fakhruddin; Taufi k Ramli; Hanif Mersil Saleh (Testing Center for Oil and Gas LEMIGAS, 2018)
Mesozoic sediments are the main objective for hydrocarbon exploration in the eastern part of Akimeugah Basin, Papua. However, little information is currently available on paleogeography and subsurface distribution of the Mesozoic rock unit. This study analyzed Mesozoic rock unit from outcrops at Wamena and surrounding area to wells data in the eastern part of Akimeugah Basin, Papua. Outcrop and well correlation was made to interpret paleogeography of Mesozoic unit. This study was using existin 2D seismic and passive seismic tomography data to determine the distribution of Mesozoic rock unit in the subsurface and its hydrocarbon potential. The Mesozoic rock unit in the eastern part of Akimeugah Basin is divided into four formations based on their lithological characteristic. Respectively from old to young, Kopai, Woniwogi, Piniya and Ekmai Formation. The depositional environment of Mesozoic rock unit in the southern part of the study area is shore/tidal to shelf and basin fl oor in the northern part. Three Mesozoic potential plays in the studied area are divided into 1) Central Range Mountains thrust-fold belt play, 2) Akimeugah low land thrust-fold belt play and 3) Tanah Merah pinch-out play. The results presented in this paper are expected to be a guide for further hydrocarbon exploration in the study area. Mesozoic sediments are the main objective for hydrocarbon exploration in the eastern part of Akimeugah Basin, Papua. However, little information is currently available on paleogeography and subsurface distribution of the Mesozoic rock unit. This study analyzed Mesozoic rock unit from outcropsat Wamena and surrounding area to wells data in the eastern part of Akimeugah Basin, Papua. Outcrop and well correlation was made to interpret paleogeography of Mesozoic unit. This study was using existing 2D seismic and passive seismic tomography data to determine the distribution of Mesozoic rock unit in the subsurface and its hydrocarbon potential. The Mesozoic rock unit in the eastern part of Akimeugah Basin is divided into four formations based on their lithological characteristic. Respectively from old to young, Kopai, Woniwogi, Piniya and Ekmai Formation. The depositional environment of Mesozoic rock unit in the southern part of the study area is shore/tidal to shelf and basin fl oor in the northern part. Three Mesozoic potential plays in the studied area are divided into 1) Central Range Mountains thrust-fold belt